Determination of vertical dimension of occlusion by using the phonetic vowel “O” and “E” - Igić, Marko; Krunić, Nebojša; Aleksov, Ljiljana; Kostić, Milena; Igić, Aleksandra; Petrović, Milica B.; Dačić, Stefan; Igić, Stevan; Igić, Aleksandar (Vojnosanitetski pregled, 2015)
Background/Aim. The vertical dimension of occlusion is a very important parameter for proper reconstruction of the relationship between the jaws. The literature describes many methods for its finding, from the simple, easily applicable clinically, to quite complicated, with the use of one or more devices for determination. The aim of this study was to examine the possibility of determining the vertical dimension of occlusion using the vocals “O” and “E” with the control of values ​​obtained by applying cognitive functions. Methods. This investigation was performed with the two groups of patients. The first group consisted of 50 females and 50 males, aged 18 to 30 years. In this group the distance between the reference points (on top of the nose and chin) was measured in the position of the mandible in the vertical dimension of occlusion, the vertical dimension at rest and the pronunciation of the words “OLO” and “ELE”. Checking the correctness of the particular value for the word “OLO” was also performed by the phonetic method with the application of cognitive exercises when the patients counted from 89 to 80. The obtained difference in the average values ​in determining the vertical dimension of occlusion and the “OLO” and “ELE” in the first group was used as the reference for determining the vertical dimension of occlusion in the second group of patients. The second group comprised of 31 edentulous persons (14 females and 17 males), aged from 54 to 85 years who had been made a complete denture. Results. The average value obtained for the vertical dimension of rest for the entire sample was 2.16 mm, for the word “OLO” for the entire sample was 5.51 mm and for the word “ELE” for the entire sample was 7.47 mm. There was no statistically significant difference between the genders for the value of the vertical dimension at rest, “ELE” and “OLO”. There was a statistically significant difference between the values ​​for the vertical dimension at rest, “OLO” and “ELE” for both genders. There was a statistically significant correlation between the value for the vertical dimension at rest, “OLO” and “ELE”, for both groups of subjects. Conclusion. Determining the vertical dimension of occlusion requires 5.5 mm subtraction from the position of the mandible in pronunciation of the word “OLO” or 7.5 mm in pronunciation of the word “ELE”.
Keywords: vertical dimension; dental occlusion; adult; cognition